(untitled) (ЕтноАнтропоЗум, 2009)
This is an attempt for auto-evaluation of the methods that were applied during a research on gossip, as well as the ethical dilemmas that surround them. The hypothesis is that probably there will never be clear professional standards that should regulate, define and educate us in the “right” or “good” way of doing ethnological and anthropological research, especially when it comes to analyzing certain segments of every-day life, such as gossip. This situation, besides implying and offering a kind of freedom, at the same time could complicate our scientific work, and make it problematic.